Neonatal vitamin D status from archived dried blood spots and future risk of fractures in childhood: results from the D-tect study, a population-based case-cohort study. Issue 1 (17th May 2017) - Händel, Mina Nicole; Frederiksen, Peder; Cohen, Arieh; Cooper, Cyrus; Heitmann, Berit Lilienthal; Abrahamsen, Bo
ABSTRACT: Background: Whether antenatal and neonatal vitamin D status have clinical relevance in fracture prevention has not been examined extensively, although observational studies indicate that fetal life may be a sensitive period in relation to bone growth and mineralization during childhood. Objective: We examined whether 25-hydroxyvitamin D3 [25(OH)D3 ] concentrations in stored neonatal dried blood spot (DBS) samples are associated with pediatric fracture risk. We hypothesized that in particular, low neonatal vitamin D status may be a risk factor for fracture incidence among children. Design: In a register-based case-cohort study design, the case group was composed of 1039 individuals who were randomly selected from a total of 82, 154 individuals who were born during 1989–1999 and admitted to a Danish hospital with a fracture of the forearm, wrist, scaphoid bone, clavicle, or ankle at age 6–13 y. The subcohort was composed of 1600 individuals randomly selected from all Danish children born during 1989–1999. The neonatal 25(OH)D3 concentrations in DBS samples were assessed by using highly sensitive chromatography-tandem mass spectrometry. Results: The mean ± SD 25(OH)D3 concentration for all subjects was 27.7 ± 18.9 nmol/L [median (IQR): 23.5 nmol/L (13.3, 37.3 nmol/L)] and showed significant monthly variation ( P < 0.0001) with the highest values in July and August. Individuals in the middle quintile of neonatal 25(OH)D3 had lower odds of sustaining a fracture than did those in the lowest quintile (adjusted OR: 0.75; 95% CI: 0.58, 0.96), but a global test did not show any significant overall association (adjusted P = 0.13). Conclusions: This study suggested that neonatal vitamin D status does not influence subsequent fracture risk in childhood. This is in accordance with studies that report no association between antenatal maternal vitamin D status and childhood fractures. Further studies are needed to examine fracture risk in relation to prenatal vitamin D status in a randomized controlled setting.